Formal description techniques, VIII proceedings of IFIP TC 6 Eighth International Conference on Formal Description Techniques, Montreal, Canada, October 1995 - Bochmann, Gregor von; Dssouli, R. (Rachida); Rafiq, Omar (Chapman & Hall on behalf of the International Federation for Information Processing (IFIP), 1996)
Contains the research results on formal description techniques applicable to telecommunications, covering their theoretical foundations, industrial applications and practical usage.